A contextual ontology for distributed urban data management. Issue 3 (12th February 2021) - Hoare, Cathal; Pinheiro, Sergio; Hu, Shushan; O'Donnell, James
Abstract : The evolution of information and communication technology in the construction domain has yielded a variety of heterogeneous data sources. While bespoke approaches have been developed to explore data merging for a variety of purposes, few have explored how to develop a multipurpose information organisation that can be reconfigured on a per-project basis. This paper describes an approach that, using a lightweight central server, is used to investigate the effectiveness of loose federations of information sources that together serve the information needs of a project. The central server provides both a common context through which relationships between the information sources can be expressed and a data register to enable information discovery. The paper describes the creation of an ontology to capture this context and a software architecture to support its use. The efficacy of the approach is illustrated through describing the use of the server for marshalling data used in a renovation project.